Protease-Activated Receptor 1 and 4 Signal Inhibition Reduces Preterm Neonatal Hemorrhagic Brain Injury. Issue 6 (June 2015) - Lekic, Tim; Klebe, Damon; McBride, Devin W.; Manaenko, Anatol; Rolland, William B.; Flores, Jerry J.; Altay, Orhan; Tang, Jiping; Zhang, John H.
<x xml:space="preserve">Abstract</x> Background and Purpose— This study examines the role of thrombin's protease-activated receptor (PAR)-1, PAR-4 in mediating cyclooxygenase-2 and mammalian target of rapamycin after germinal matrix hemorrhage. Methods— Germinal matrix hemorrhage was induced by intraparenchymal infusion of bacterial collagenase into the right ganglionic eminence of P7 rat pups. Animals were treated with PAR-1, PAR-4, cyclooxygenase-2, or mammalian target of rapamycin inhibitors by 1 hour, and ⩽5 days. Results— We found increased thrombin activity 6 to 24 hours after germinal matrix hemorrhage, and PAR-1, PAR-4, inhibition normalized cyclooxygenase-2, and mammalian target of rapamycin by 72 hours. Early treatment with NS398 or rapamycin substantially improved long-term outcomes in juvenile animals. Conclusions— Suppressing early PAR signal transduction, and postnatal NS398 or rapamycin treatment, may help reduce germinal matrix hemorrhage severity in susceptible preterm infants.